1995
DOI: 10.4037/ajcc1995.4.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous lateral rotation therapy on pulmonary complications in liver transplant patients

Abstract: BACKGROUND: When liver transplant candidates and recipients suffer from pulmonary complications of immobility, the results can be life-threatening. Continuous lateral rotation therapy has been reported to decrease complications of immobility. OBJECTIVES: To determine whether continuous lateral rotation therapy decreases the duration of mechanical ventilation, intensive care unit length of stay, incidence or resolution of atelectasis, incidence or onset time of lower respiratory tract infection and pneumonia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…[1][2][3][4] Reports have described the use of CLRT to decrease the duration of mechanical ventilation and the incidence of lower respiratory tract infection and increase the length of time before the development of respiratory tract infection and pneumonia. [1][2][3][4] Hepatopulmonary syndrome (HPS) is a known sequela of liver failure that is characterized by liver disease, pulmonary vascular dilation, and abnormal arterial oxygenation, which can result in severe hypoxemia. 5 It was previously considered to be a relative contraindication to orthotopic liver transplantation (OLT) because of the increased risk for mortality, both in the perioperative and postoperative periods.…”
Section: Copyright 1998 By the American Association For The Study Of mentioning
confidence: 99%
“…[1][2][3][4] Reports have described the use of CLRT to decrease the duration of mechanical ventilation and the incidence of lower respiratory tract infection and increase the length of time before the development of respiratory tract infection and pneumonia. [1][2][3][4] Hepatopulmonary syndrome (HPS) is a known sequela of liver failure that is characterized by liver disease, pulmonary vascular dilation, and abnormal arterial oxygenation, which can result in severe hypoxemia. 5 It was previously considered to be a relative contraindication to orthotopic liver transplantation (OLT) because of the increased risk for mortality, both in the perioperative and postoperative periods.…”
Section: Copyright 1998 By the American Association For The Study Of mentioning
confidence: 99%
“…Data from these studies support the use of CLRT in critically ill patients, although it should be noted that manufacturer involvement may have introduced bias into the study. Whiteman et al (1995) found that the increased cost of CLRT is offset by reduced nosocomial pneumonia and antibiotic use and a decreased length of stay in the hospital and the ICU. Sahn (1991) reviewed the results of four prospective randomized studies (36-39) and two retrospective analyses.…”
Section: Respiratory Carementioning
confidence: 99%
“…Alguns estudos relataram benefícios da TR para diferentes condições em pacientes hospitalizados: com disfunções pulmonares 17,18 , com lesão cerebral 19 , com lesão medular 20,21 , com transplante hepático 22 , com acidente vascular cerebral 23,24 , entre outros. No entanto, esse recurso ainda é pouco difundido entre os profissionais de saúde e hospitais, não sendo utilizado rotineiramente.…”
Section: N T R O D U ç ã Ounclassified